Electrochemical Behavior and Reclamation of Beryllium Scrap in Molten Salt - Yuzhen Chen; Shaolong Li; Zepeng Lv; Wen Luo; Peng Qiao; Dongxin Wang; Jilin He; Jianxun Song (ChemElectroChem)
Abstract Beryllium is a crucial strategic metal characterized by its exceptional properties, which has facilitated its extensive application across various high‐tech industries. However, despite advancements in refining techniques, the purification of industrial‐grade beryllium scrap remains insufficiently explored. This gap has led to challenges such as resource waste and environmental concerns. This study aims to bridge this gap by investigating the electrolytic refining process of beryllium scrap through molten salt electrolysis. Linear sweep voltammetry (LSV), cyclic voltammetry (CV), and square wave voltammetry (SWV) are employed to analyze both anodic dissolution and cathodic reduction behaviors. The study demonstrates that beryllium undergoes a single‐step, two‐electron transfer reduction process, while impurity elements are separated as anodic slime. The effects of current density on beryllium deposition morphology and removal efficiency have been further investigated. This research provides a novel approach to beryllium scrap purification, contributing significantly to the optimization of the beryllium supply chain and offering valuable insights into sustainable metal refinement practices.